THE EFFECT OF EARNING PER SHARE (EPS) AND RETURN ON EQUITY (ROE) ON STOCK PRICES WITH INFLATION AS MODERATING VARIABLE (Study on Financing institutions listed on the Indonesian Stock Exchange 2012-2021 Period) - Rizkina, Zahira; Mahmudi, Bambang; Khaerunnisa, Enis (Management Science Research Journal, 2023)
Financing institution play a large role for the people of a country in the process of distributing fund as a driver of the economy. In financial institutions, share prices play an important role as a barometer of company success. This study aims to determine the effect of Earning Per Share (EPS) and Return On Equity (ROE) on stock prices with inflation as a moderating variable in financial institution companies listed on the Indonesia Stock Exchange during the period 2012-2021. This research used a purposive sampling technique with a sample size of 7 samples from 18 financial institution companies, so that the research data analyzed amounted to 70 data. This research uses the SPSS V.20 application as a data analysis tool which will be described using descriptive statistical methods, classical assumptions, hypothesis testing, and Moderate Analysis Regression (MRA). The research result obtained partially show that EPS a positive and significant influence on stock prices. ROE and inflation have a negative and significant influence on stock prices. And partially, inflation is able to moderate the relationship between EPS on share prices. And inflation is unable to moderate ROE on share prices in financial institution companies.